SHANGHAI - Bregnbæk, Susanne (Tidsskriftet Antropologi, 2003)
The article traces the image of Shanghai as the whore of the East. Taking Ian Buruma and Avishai Margalit’s thoughtprovoking book Occidentalism (2003) as a point of departure, the author explores how Shanghai because of its close relationship to the West, epitomises a Chinese ambiguous relationship between modernity and tradition. Since the beginning of the twentieth century Shanghai has been associated with the promiscuous good-life of the English and French colonial elite. Mao saw Shanghai as the “most Western whore of them all” and by waging war on the city he put an end to the decadent period of Western imperialism. Today Shanghai is an impressive and at the same time uncanny monument of China’s economic growth and a symbol of modernity. The article suggests that imaginings of Shanghai are telling of China’s attempt to develop modernity with Chinese characteristics. Shanghai’s revival as the new face of China being a centre of economic growth and cosmopolitanism has, however, given rise to a new fear of Westernisation. Despite efforts to control the social world including social spaces, changing lifestyles pose new threats to the Communist Party’s wish for monopoly of the definition of social reality. This becomes clear in a controversy over the novel Shanghai Baby, which plays on Shanghai’s previous image as the whore of the East in a modern guise.